2022
DOI: 10.1093/nutrit/nuab104
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effects of Hibiscus sabdariffa on blood pressure and cardiometabolic markers

Abstract: Context Hibiscus sabdariffa (hibiscus) has been proposed to affect cardiovascular risk factors. Objective To review the evidence for the effectiveness of hibiscus in modulating cardiovascular disease risk markers, compared with pharmacologic, nutritional, or placebo treatments. Data Sources A systematic search of the Web of Science, Cochrane, Ovid (MEDLINE, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Hibiscus sabdariffa (HS), also known as Roselle or red tea, is a member of the Malvaceae family, with a unique anthocyanin profile containing delphinidin-and cyanidin-sambubiosides as main anthocyanin compounds. Intake of HS has been associated with lowering of blood pressure and blood cholesterol [12]; indeed, a recent meta-analysis of our group has confirmed the consistent effect of HS on systolic blood pressure reduction [13]. The potential anti-diabetic effects of HS have received much less attention with so far limited research being conducted.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Hibiscus sabdariffa (HS), also known as Roselle or red tea, is a member of the Malvaceae family, with a unique anthocyanin profile containing delphinidin-and cyanidin-sambubiosides as main anthocyanin compounds. Intake of HS has been associated with lowering of blood pressure and blood cholesterol [12]; indeed, a recent meta-analysis of our group has confirmed the consistent effect of HS on systolic blood pressure reduction [13]. The potential anti-diabetic effects of HS have received much less attention with so far limited research being conducted.…”
Section: Introductionmentioning
confidence: 69%
“…Importantly, long-term effects on glucose metabolism will need to be established. Our recent systematic review and meta-analysis of chronic HS intervention trials has found no differences in fasting blood glucose among the small number of studies on this topic, however the direct comparison was not possible due to variations in study design and in control groups [13]. Therefore, further studies investigating chronic effects of HS intake on markers of glycaemia are urgently needed.…”
Section: Discussionmentioning
confidence: 98%
“…An overview of the adverse health effects, which have been associated with HCA and HCA in plant preparations in the scientific literature was prepared based on available risk assessments of dietary HCA from various organizations (FDA, 2009; ANSM, 2012; AESAN, 2019; ANSES, 2022) (Appendix C) and reviews (Soni et al, 2004;Onakpoya et al, 2011;Bakhiya et al, 2017;Maunder et al, 2020;Payab et al, 2020;Andueza et al, 2021;Ellis et al, 2022). Several adverse events were identified from case reports and case series (Actis et al, 2007;Elinav et al, 2007;Jones and Andrews, 2007;Fong et al, 2010;Narasimha et al, 2013;Lopez et al, 2014;Araujo and Worman, 2015;Mancano, 2015;Beecheno et al, 2016;Corey et al, 2016;Hendrickson et al, 2016;Lunsford et al, 2016;Wong et al, 2016;Cotovio and Oliveira-Maia, 2017;Crescioli et al, 2018;Kothadia et al, 2018;Nguyen et al, 2019;Nilsson and Duan, 2019;Ferreira et al, 2020;Khetpal et al, 2020).…”
Section: Identification Of Relevant Endpointsmentioning
confidence: 99%
“…Meta-analysis of five studies (n = 285) of G. cambogia as a single herb produced a non-significant effect on weight, with an Standardized mean difference (SMD) +0.04(95% CI-0.33, +0.41; P= 0.82) compared to placebo (I²=56%). Preparations containing G. cambogia did not have a significant effect on weight (I²=87%) Blood pressure, Hypotension (Ellis et al, 2022) Meta-analysis of randomized controlled trials Search was conducted until June 2021 on randomized controlled trials using Hibiscus sabdariffa as an intervention for lipid profiles, blood pressure (BP), and fasting plasma glucose levels in adult populations. Hibiscus exerted stronger effects on systolic BP (−7.10 mmHg [95%CI, −13.00, −1.20]; I2 = 95%; P = 0.02) (n=12 studies) than placebo, with the magnitude of reduction greatest in those with elevated BP at baseline.…”
Section: Hibiscus Sanguineus Griffmentioning
confidence: 99%
“…RYR extracts have been proven beneficial for lipid modification (Lu et al, 2008;Cicero et al, 2019). Hibiscus sabdariffa was also helpful for dyslipidemia (Sabzghabaee et al, 2013;Ellis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%